Formation of integrated mechanisms for scientific and technical cooperation in EAEU (Journal of Economic Research & Business Administration, 2017)
Implementation of the priorities of mutual satisfaction within the EAEUdemand for innovation and high-tech products creates a basis for the organizationaland economic programming of the international competitivenessof science and technology complexes of EAEU member states in orderto create new types of industries in the scientific and technological basisof strategic innovation programs pool. This requires a layout of complexprocesses of managing a large number of business units involved in theinnovation processes that can be effectively structured under the conceptof creating a Eurasian-allied networks of innovation clusters to form a newtechnological base using core market-shaping innovation through the implementationof a strategic pool of innovative programs.
Keywords: innovation; research and technological development; information systems; strategic management.